Trend dominance in macroeconomic fluctuations - Katsuyuki Shibayama (University of Kent, School of Economics, 2015)
This paper investigates multivariate Beveridge-Nelson decomposition of key macro aggregate data. We find (a) inflation seems to be dominated by its trend component, and, perhaps as a result of this, the short-term interest rate is also trend dominated; and (b) consumption also seems to be dominated by its trend component perhaps as the permanent income hypothesis suggests. What is new here is that, although the difficulty of rejecting a unit root for these variables has been long recognized, we show that these unit root processes account for a large share of the variable fluctuations. This result raises a concern about the convention that the non-stationary data is detrended in standard DSGE-type structural estimation, in the sense that a significant portion of data variation actually may come from the trend components.
Keywords: C32; E21; E31; E32; E52; 330; Beveridge-Nelson Decomposition; DSGE; VECM; Detrending